Biotransformation of fluorophenyl pyridine carboxylic acids by the model fungus Cunninghamella elegans. (2nd September 2017) - Palmer-Brown, William; Dunne, Brian; Ortin, Yannick; Fox, Mark A.; Sandford, Graham; Murphy, Cormac D.
Abstract: 1. Fluorine plays a key role in the design of new drugs and recent FDA approvals included two fluorinated drugs, tedizolid phosphate and vorapaxar, both of which contain the fluorophenyl pyridyl moiety. 2. To investigate the likely phase-I (oxidative) metabolic fate of this group, various fluorinated phenyl pyridine carboxylic acids were incubated with the fungus Cunninghamella elegans, which is an established model of mammalian drug metabolism. 3.  19 F NMR spectroscopy established the degree of biotransformation, which varied depending on the position of fluorine substitution, and gas chromatography–mass spectrometry (GC–MS) identified alcohols and hydroxylated carboxylic acids as metabolites. The hydroxylated metabolites were further structurally characterised by nuclear magnetic resonance spectroscopy (NMR), which demonstrated that hydroxylation occurred on the 4′ position; fluorine in that position blocked the hydroxylation. 4. The fluorophenyl pyridine carboxylic acids were not biotransformed by rat liver microsomes and this was a consequence of inhibitory action, and thus, the fungal model was crucial in obtaining metabolites to establish the mechanism of catabolism.